Seasonal Variations in the Biological Value of Kyrgyz Donkey’s Milk Proteins - Nadira K. Turganbaeva; Mukarama M. Musulmanova; Nurudin A. Kydyraliev (Техника и технология пищевых производств)
Due to its protein component, donkey’s milk is a multifunctional product with a wide range of beneficial physiological properties. It is known for its antioxidant, anti-inflammatory, rejuvenating, antimicrobial, and antitumor effects. However, the milk of Kyrgyz donkeys has not received proper scientific attention in this respect. This study analyzed the seasonal amino acid profile and biological value of milk obtained from Kyrgyz donkeys. The donkeys belonged to the Kyrgyz breed and inhabited the highlands of the Chui Region, Republic of Kyrgyzstan. The sampling took place in April, July, and September. The amino acid composition of milk proteins was determined by capillary electrophoresis. The biological value of proteins was assessed by amino acid score, index of essential amino acids (Auxerre index), utility ratio of essential amino acids, and utility ratio of amino acid composition. The analysis revealed 18 amino acids, including eight essential ones. The total content of amino acids in the spring samples was 1840.07 mg/100 g. In the summer samples, this value peaked at 2037 mg/100 g; in autumn, it dropped to 1264.35 mg/100 g. The changes could be explained by the seasonal differences in the diet. The ratio of essential to non-essential amino acids approached 1:1. The milk also proved to contain arginine, which is an essential amino acid for a juvenile organism. In the spring samples, its content was 2.5 times as big as in the autumn ones. Leucine and isoleucine were responsible for 1/3 of the essential amino acids (322.60 ± 19.35 mg/100 g). The summer samples demonstrated the maximal content of some other essential amino acids, except for valine and tryptophan, which appeared to be the limiting essential amino acids for donkey’s milk in the autumn period. Total essential amino acids in the spring, summer, and autumn samples amounted to 54.24, 59.26, and 34.77 g/100 g, respectively, which exceeded the value for the reference protein (27.46 g/100 g). Kyrgyz donkey’s milk proteins were of high biological value, regardless of the season, which means that donkey’s milk can become part of new functional products.